Real time IR based Indoor Environment Monitoring and Control System - Kodukula Ramakanth, Korai Mohit, R. Raj Kumar, Radhakanth Kodukula (International Journal of Advanced Science and Technology, 2020)
Electronic gadgets have become an integrated part of lives nowadays. The Internet has become one of the things which is being used as the most common and important thing now and will be in the future too. Internet of things (IoT) is the future of this world with numerous features and it has unlimited and extensive expandability. Anything can be triggered with the use of a microcontroller which is connected with some basic sensors to it with some basic script. Now coming to the concept of a “Controlling home appliances with Smart glasses”, one can basically control any appliance in the house such as fan, tubelight, television etc. with IR signals. Here, we use a basic IR sensor which is attached to a modified spectacles and the frequency level of the sensor will be configured in such a way that the IR receiver gets the signal from the transmitter. We can set some specified /separate timer and frequency code for different appliances so that it alone turns on keeping the rest untouched while operating. So, by adding these separate timers for each different appliance we can easily control them with the IR sensors. We can connect all the appliances to the relay board which will be further connected to an Arduino. This system can also be controlled via the Internet using a simple NodeMCU and Blynk web server and application. When the above mentioned cases do not work we can switch over to Bluetooth which controls the appliances locally within the proximity range. So, by integrating all the use cases of the above mentioned system with an XOR IC chip, we can control and monitor a single device using all the techniques involved